2006
DOI: 10.1523/jneurosci.3576-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and the Emotional Brain: Specific Brain Activity Associated with Spontaneous Fluctuations of Intensity of Chronic Back Pain

Abstract: Living with unrelenting pain (chronic pain) is maladaptive and is thought to be associated with physiological and psychological modifications, yet there is a lack of knowledge regarding brain elements involved in such conditions. Here, we identify brain regions involved in spontaneous pain of chronic back pain (CBP) in two separate groups of patients (n ϭ 13 and n ϭ 11), and contrast brain activity between spontaneous pain and thermal pain (CBP and healthy subjects, n ϭ 11 each). Continuous ratings of fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
555
11
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(604 citation statements)
references
References 49 publications
33
555
11
5
Order By: Relevance
“…For patients with lower pain level, it is possible that the sensorimotor cortex does not show pathophysiological modification or is less alerted when compared to patients with higher pain intensity. Indeed, several neuroimaging studies have demonstrated the correlation between pain intensity and degree of abnormal activity and connectivity within areas of the pain matrix in various chronic pain syndromes [60,64,65]. Future research to identify biomarkers and predictors of tDCS response could help to identify who and why some patients could benefit from this treatment, as well as to develop a patient-tailored stimulation protocol.…”
Section: Patients With Higher Pain Levels Seem To Respond Better To Tdcsmentioning
confidence: 99%
“…For patients with lower pain level, it is possible that the sensorimotor cortex does not show pathophysiological modification or is less alerted when compared to patients with higher pain intensity. Indeed, several neuroimaging studies have demonstrated the correlation between pain intensity and degree of abnormal activity and connectivity within areas of the pain matrix in various chronic pain syndromes [60,64,65]. Future research to identify biomarkers and predictors of tDCS response could help to identify who and why some patients could benefit from this treatment, as well as to develop a patient-tailored stimulation protocol.…”
Section: Patients With Higher Pain Levels Seem To Respond Better To Tdcsmentioning
confidence: 99%
“…7,26,27 Activation in the medial prefrontal cortex was reported during ongoing lower back pain, and was correlated with the intensity of the pain. 28 The thalamus is another region affected by chronic pain. Several studies reported a decrease of cerebral blood flow and metabolic rate in the thalamus contralateral to the clinical pain.…”
Section: Experimental and Clinical Pain: Same Or Different Brain Regimentioning
confidence: 99%
“…28 However, the increase of the intensity of their clinical pain correlates with activation in the regions observed during acute pain processing (i.e., the somatosensory cortices and the insular cortex). 28 Kulkarni et al 44 also observed differences between ongoing arthritic pain and evoked pain.…”
Section: Evoked Versus Spontaneous Pain In Chronic Pain Patientsmentioning
confidence: 99%
“…In humans, different subregions of the PFC have a role in acute pain; the medial prefrontal cortex (mPFC) was found to be involved in signaling the unpleasantness of pain (3); the anterior cingulate cortex mediates the affective component of pain responses (4) and the placebo effect (5); and anticipation of pain is positively correlated with activity in both the anterior cingulate and mPFC (6). Lending support to the hypothesis that chronic pain involves cortical reorganization, functional MRI (fMRI) studies in patients with complex region pain syndrome type I (CRPS-I) and back pain have shown that the patients' real-time rating of perceived intensity of spontaneous pain is associated with novel activity in mPFC (7,8) when compared with activity patterns that correlate with rating of acute pain stimuli. Additionally, studies in humans with CRPS-I and chronic back pain demonstrate impaired performance on emotional decisionmaking tasks such as the Iowa Gambling Task (9), which implies involvement of the mPFC.…”
mentioning
confidence: 99%